On the (de)stabilizing effects of news shocks - Roland C. Winkler; Hans-Werner Wohltmann (Kiel Institute for the World Economy (IfW), 2009)
This paper analyzes the impacts of news shocks on macroeconomic volatility. Whereas anticipation amplifies volatility in any purely forward-looking model, such as the baseline New Keynesian model, the results are ambiguous when including a backward-looking component. In addition to these theoretical findings, we use the estimated model of Smets and Wouters (2003) to provide numerical evidence that news shocks increase the volatility of key macroeconomic variables in the euro area when compared to unanticipated shocks.
Keywords: E32; 330; Anticipated Shocks; Business Cycles; Volatility; Schock; Konjunktur; Volatilität; Europäische Wirtschafts- und Währungsunion; Theorie; EU-Staaten